HTR-Based Power Plants' Performance Analysis Applied on Conventional Combined Cycles. (3rd March 2015) - Carril, José Carbia; Insua, Álvaro Baaliña; Gómez, Javier Romero; Gómez, Manuel Romero
Abstract : In high temperature reactors including gas cooled fast reactors and gas turbine modular helium reactors (GT-MHR) specifically designed to operate as power plant heat sources, efficiency enhancement at effective cost under safe conditions can be achieved. Mentioned improvements concern the implementation of two cycle structures: (a), a stand alone Brayton operating with helium and a stand alone Rankine cycle (RC) with regeneration, operating with carbon dioxide at ultrasupercritical pressure as working fluid (WF), where condensation is carried out at quasicritical conditions, and (b), a combined cycle (CC), in which the topping closed Brayton cycle (CBC) operates with helium as WF, while the bottoming RC is operated with one of the following WFs: carbon dioxide, xenon, ethane, ammonia, or water. In both cases, an intermediate heat exchanger (IHE) is proposed to provide thermal energy to the closed Brayton or to the Rankine cycles. The results of the case study show that the thermal efficiency, through the use of a CC, is slightly improved (from 45.79% for BC and from 50.17% for RC to 53.63 for the proposed CC with He-H2 O operating under safety standards).